Efficacy and safety of 0.1% ciclosporin A cationic emulsion in dry eye disease: a pooled analysis of two double-masked, randomised, vehicle-controlled phase III clinical studies. Issue 1 (15th March 2018) - Leonardi, Andrea; Messmer, Elisabeth M; Labetoulle, Marc; Amrane, Mourad; Garrigue, Jean-Sébastien; Ismail, Dahlia; Sainz-de-la-Maza, Maite; Figueiredo, Francisco C; Baudouin, Christophe
Abstract : Background/aim: To assess the treatment effect of 0.1% ciclosporin A cationic emulsion (CsA CE) versus vehicle on signs/symptoms of dry eye disease (DED) in various subgroups (moderate-to-severe DED/severe DED/Sjögren's syndrome (SS)/SS with severe DED). Methods: Pooled data were analysed from two similar phase III studies: SICCANOVE (moderate-to-severe DED) and SANSIKA (severe DED with severe keratitis). In both studies, patients aged ≥18 years received CsA CE 0.1% (n=395) or vehicle (n=339) once daily for 6 months. A composite responder efficacy endpoint (corneal fluorescein staining–Ocular Surface Disease Index (CFS–OSDI) at month 6) was used to evaluate the efficacy of CsA CE in alleviating signs/symptoms of DED (response defined as improvement of ≥2 grades in CFS and ≥30% in OSDI (baseline to month 6)). Human leucocyte antigen-DR (HLA-DR) conjunctival expression was used as a biomarker of ocular surface inflammation. Results: CsA CE–treated patients were significantly more likely to be CFS–OSDI responders than vehicle-treated patients in the overall (OR 1.66, 95% CI 1.11 to 2.50; P=0.015), severe DED (1.80, 1.04 to 3.19; P=0.038) and SS with severe DED (3.37, 1.20 to 11.19; P=0.030) populations. The difference was not significant for CsA CE versus vehicle for the overall Sjögren's population (OR 1.77, CI 0.89 to 3.66; P=0.109). CsA CE also significantly reduced median HLA-DR expression versus vehicle at 6 months (P=0.002). Conclusion: Pooled phase III data indicate CsA CE produced significant improvement in signs/symptoms versus vehicle in patients with moderate-to-severe DED (especially in those with severe keratitis), including patients with SS with severe DED.